Social capital determinants of preferential resource allocation in regional clusters - Niels J. Pulles; Holger Schiele (Management Revue, 2013)
Regional clusters are known to facilitate firms in achieving higher levels of competitive advantage. This observation suggests that cluster firms manage to obtain better competitive resources than firms outside the cluster. The strong social ties in regional clusters are considered to be a crucial factor in the resource exchange between cluster firms. In this paper, we integrate this social perspective from the cluster literature with a recent stream in the resource-based view (RBV) literature. This stream seeks to explain the phenomenon of preferential resource allocation. That is, how can firms obtain better resources from a resource environment that is shared with competitors? Although preferential resource allocation has revealed to be a relevant concept, little is known about its actual antecedents. We introduce a conceptual framework that builds on the social interactions among cluster firms to explain the concept of preferential resource allocation. More specifically, we develop propositions on the antecedents of preferential resource allocation by building on the structural, relational, and cognitive dimensions of social capital theory, and a firm' s embeddedness in a regional cluster. In so doing, this paper provides insights that may contribute to a better understanding of the competitive advantage of cluster firms, and it opens onto current streams in the RBV literature.
Keywords: L10; 650; regional clusters; preferential resource allocation; resource competition; inter-firm resource exchange; Regionales Cluster; Social Capital; Allokation; Ressourcenorientierter Ansatz